Application of Naïve Bayes Method for Student Performance Classification - Prayoga, Riza Akhsani Setyo; Basatha, Rizky; Akbar, Muhammad Sonhaji; Elfaiz, Ersha Aisyah; Putra, Cendra Devayana (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
In every school, students exhibit varying levels of performance, influenced by several factors such as parental support and involvement, participation in extracurricular activities, motivation levels, internet access for learning, teacher quality, peer influence, and learning difficulties. This study aims to classify student performance to identify those who may need additional support for improvement. The classification method employed in this research is the Naïve Bayes algorithm. The results indicate that the trained model successfully classified 25 out of 30 tested data points. The evaluation metrics achieved include a precision of 100%, recall of 80%, specificity of 100%, accuracy of 83%, and an F1-score of 89%.